THE IMPORTANCE OF TAX PAYMENTS IN THE DEVELOPMENT OF SMALL BUSINESS - Axrorov Abbos Aslamjon o’g’li,; Salimova Sevinch Bekzod qizi,; Aliqulov Musurmon Kamoliddin o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  provides  a  comprehensive  analysis  of  the  economic importance of tax payments in the development of small business. In particular, the impact of tax policy on the activities of small business entities, as well as its role in increasing  their  financial  stability  and  investment  attractiveness,  is  scientifically substantiated. As of 2026, in many countries, including Uzbekistan, mechanisms such as optimizing the tax burden, granting benefits, and introducing simplified tax systems are widely applied in order to stimulate economic growth and support small business. The  article  also  notes  that  in  2026,  the  share  of  small  business  in  GDP  in  many developing  countries  is  around  50–60%,  while  in  Uzbekistan  this  indicator  has approached 55%. This indicates the need for further improvement of tax policy. In conclusion, it is substantiated that effective tax mechanisms are an important factor in the development of small business.